Diuretics and mortality reduction in incident dialysis patients: a two-year observational study - Maxime Ingwiller; Dogan-Firat Bozman; Nans Florens; Damiano Cerasuolo; Cécile Vigneau; Cécile Couchoud; Thierry Hannedouche (Scientific Reports)
Abstract Fluid overload predicts morbidity and mortality in dialysis patients. Diuretics can reduce fluid overload, but their effects on morbi-mortality following inception remain ill-defined. To determine whether diuretics reduce mortality and hospitalization rates in incident dialysis patients in the first 2 years after inception. Adult patients starting dialysis between 2009 and 2015 in the REIN registry were matched with the SNDS database and divided into four subgroups according to loop diuretics exposure: < 5%, 5–50%, 50–80% or > 80% over the observation period of each patient. The incidence of hospitalization was described based on the primary diagnoses of the discharge summaries and codes. In this study, which included 67,736 patients, 53,829 (79.5%) who had varying degrees of diuretic exposure exhibited a significantly lower mortality rate at 2 years compared to those without diuretic exposure (24.8% [95% CI 24.4–25.2], vs 37.5% [95% CI 36.7–38.3] respectively). However, the duration of diuretic exposure significantly impacted outcomes. The all-cause mortality rate at two years was highest in the group with ≥ 80% exposure (68.2% [95% CI 67.3–69.1]), followed by those with 50–80% exposure (15.7% [95% CI 15.0–16.4]), and those with 5–50% exposure (6.6% [95% CI 6.3–7.0]). An inverse probability weighting (IPW) propensity score analysis supported these findings. Stratified analyses showed consistent results regardless of a history of congestive heart failure and were similar for both hemodialysis and peritoneal dialysis patients. Additionally, the number of hospitalizations and length of stay were generally higher in the group with the longest exposure to loop diuretics. Diuretic exposure was generally associated with a lower mortality rate in dialysis patients. However, prolonged exposure (≥ 80%) was linked to an increased risk of mortality and hospitalization. This prolonged exposure may indicate residual diuresis at the cost of chronic fluid overload.